2021
DOI: 10.1093/jscr/rjab036
|View full text |Cite
|
Sign up to set email alerts
|

Femoral hernia with vermiform appendix herniation: a case report and review of the literature

Abstract: Femoral hernias constitute 2–4% of all groin hernia repairs. Herniation of the vermiform appendix into the femoral hernia sac is rare. The majority of patients with appendix hernias are asymptomatic and diagnosis is made intraoperatively. We report about a case of a female patient presenting with an irreducible right-sided femoral hernia without symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…It has been suggested that the Ventral Hernia Working Group grading platform and Centers for Disease Control and Prevention surgical wound classification system be used to individualize and guide patient treatment 7 . Whether to perform an appendicectomy is also unclear, but even if the appendix is macroscopically normal, microscopic inflammation and/or stenosis secondary to incarceration and inflammation within the hernia neck cannot be excluded 2 . This being a rare presentation, a randomized trial is not possible.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that the Ventral Hernia Working Group grading platform and Centers for Disease Control and Prevention surgical wound classification system be used to individualize and guide patient treatment 7 . Whether to perform an appendicectomy is also unclear, but even if the appendix is macroscopically normal, microscopic inflammation and/or stenosis secondary to incarceration and inflammation within the hernia neck cannot be excluded 2 . This being a rare presentation, a randomized trial is not possible.…”
Section: Figmentioning
confidence: 99%
“…This being a rare presentation, a randomized trial is not possible. The literature suggests the use of mesh is a safe option in clean or clean‐contaminated fields (such as a normal or mildly inflamed appendix) for a patient with few risk factors for surgical site infections 2,3,7 …”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…The ultrasonography, computed tomography and magnetic resonance imaging help in identifying doubtful cases [6,9]. It can help in preoperative diagnosis of complications like the presence of appendicitis within femoral hernial sac [2].…”
Section: Diagnostic Imagingmentioning
confidence: 99%